Assessing efficacy and safety of iron (III) hydroxide oligoisomaltosate in reproductive-age women with iron deficiency anemia - M. D. Andreeva; A. N. Akhidzhak; A. D. Belaya; L. Yu. Karakhalis; T. S. Kononenko (Акушерство, гинекология и репродукция, 2023)
Aim: to demonstrate efficacy and safety of iron (III) hydroxide oligoisomaltosate in patients with iron deficiency.  Materials and Methods. An observational cohort study was conducted: 31 patients were examined – 10 puerpera patients, 13 pregnant women, 8 gynecological patients suffering from iron deficiency anemia, stage 1–3. After further examination (biochemical blood test – ferritin, iron, latent iron binding capacity, total calcium, inorganic phosphorus, transferrin, C-reactive protein), therapy with "Monofer" (iron (III) hydroxide oligoisomaltosate) was performed. Four weeks after the final drug administration, the efficacy and patient satisfaction were monitored.  Results. During the examination, significant changes in the following parameters were found: erythrocyte count increased after therapy by 1.3-fold, hemoglobin – by 26.5 g/L, hematocrit – by 0.58 % (p = 0.00). Biochemical blood test data also showed positive dynamics: ferritin was higher by 216.21 ng/ml, latent iron binding capacity – lower by 30.73 µmol/l, transferrin – lower by 1.17 g/L, iron level – higher by 6.87 µmol/l, modestly increased total calcium – by 0.14 mmol/l, and inorganic phosphorus – by 0.1 mmol/l. Patients surveyed according to the Likert scale showed a high degree of satisfaction with treatment. No adverse effects (AE) and Serious Adverse Effects (SAE) occurred during the study.  Conclusion. A significant increase in the parameters of the qualitative and quantitative composition of blood cell count and biochemical parameters has been achieved. Posttransfusion hypophosphatemia and hypocalcemia were not observed in the studied patients. High satisfaction with the treatment and drug safety in patients were noted.